Pengaruh Komunikasi dan Struktur Organisasi Terhadap Kinerja Pengurus Organisasi Mahasiswa (Studi Kasus Himpunan Mahasiswa Program Studi Manajemen Universitas Islam Malang Periode 2022) - Irfan Efendi; Budi Wahono; Andi Normala (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study was to determine the effect of communication and organizational structure on the performance of HimaProdi Unisma Management. The type of research used is explanatory research with a quantitative approach. The sample in this study amounted to 53 respondents with the technique used in this study purposive sampling. The results showed that the results of the f test of communication and organizational structure simultaneously had a positive and significant effect on performance. From the results of the t-test analysis, it is known that the communication variable has a positive and significant effect on performance and the organizational structure variable has a positive and significant effect on performance.  Keywords: communication, organizational structure, performance